Pseudo-Dynamic Tests on a Full-Scale Four-Storey Reinforced Concrete Frame Seismically Retrofitted with Reinforced Concrete Infilling - Chrysostomou, Christis; Poljanšek, Martin; Kyriakides, Nicholas; Taucer, Fabio; Molina, Francisco Javier (My University, 2013)
The effectiveness of seismic retrofitting of multi-storey multi-bay reinforced concrete (RC)-frame buildings by converting selected bays into new walls through infilling with RC was studied experimentally at the ELSA facility of the Joint Research Centre in Ispra (Italy). A full-scale model was tested with the pseudo-dynamic (PsD) method and consisted of two four-storey (12 m tall) three-bay (8,5 m long) parallel frames linked through 0,15 m slabs with the central bay (2,5 m) infilled with an RC wall. The frames were designed and detailed for gravity loads only and were typical of similar frames built in Cyprus in the 1970s. Different connection details and reinforcement percentages for the two infilled frames were used in order to study their effects in determining structural response. The results of the pseudo-dynamic and cyclic tests performed on the specimen are presented, and conclusions are drawn.
Keywords: FRP Strengthening of deficient LAP-SPLICES; Full scale cycling-testing; Full scale pseudo-dynamic testing; RC infill walls; Retrofitting existing structures